Comparing the Effect of Topical Acidulated Phosphate Fluoride on Micro- Hardness of Two Fissure Sealants and One Flowable Composite - Mazaheri, Romina; Pishevar, Leila; Keyhanifard, Neda; Ghasemi, Elnaz (Journal of Dental School, 2019)
Objective: Probable effect of fluoride containing materials like APF on sealants is very important. The purpose of this study is to assess the effect of frequent application of APF (1.23%) on the surface microhardness of two fissure sealants and one flowable composite. Methods: In this experimental study, 81 specimens of two fissure sealants and one flowable composite were prepared, using special polymer mold in three groups of 27 including unfilled resin sealant (Fissurite F, Voco), filled resin sealant (Fissurit FX, Voco) and one flowable composite (Arabesk Flow, Voco). Then, these three groups were divided into three sub groups of 9 as follows: Group 1, 4, 7 (control): No treatment- Group 2, 8, 5: Single application using APF- Group 3, 6, 9: Six times application using APF. The APF was applied on the experimental specimens every time for 4 minutes. Then, the samples were stored in the distilled water. Finally, the surface microhardness of the sealants was measured using Vickers test. The statistical analysis was performed by 2-way ANOVA & One-way ANOVA tests. Results: Type of materials (without filler, containing filler and flowable composite) was effective on the surface microhardness and the difference between three types of materials was statically significant (p<0.001).Unfilled fissure sealants, showed minimum surface microhardness and flow able composite showed maximum surface microhardness. Also, the frequency of gel use (once or many times), had no effect on the average surface microhardness of the materials under review (p>0.05). Conclusion: All three materials were resistant to the destructive effects of APF gel and it did not make a significant microhardness changes.